A review on the law of incest in Malaysia / Noor Hafiza Ishak … [et al.] - Ishak, Noor Hafiza; Khairulnizam, Nuraina Afiqah; Hasnan, Nur Sabrina; Abd Muis, Siti Nuralis (2014)
Incest is an offence that is viewed with disgust and abhorrence. The term incest is not alien to Malaysia as the number of incest crime in Malaysia is worrying. A glance at the statistical sketch reported to the Malaysian Police does indicate the increment of incest offence. However, the Royal Malaysia Police Department revealed that there are still many incest cases that go unreported as reports only being lodged as a last resort. This research paper is designed to study and analyse the efficacy of the existing law of incest in Malaysia as provided under the Penal Code. This study also highlights the root which cause the worrying number of incest cases and also underline several theoretical and pragmatic issues associated with the criminalization of incest in Malaysia which are the imprecise definition of incest and the insufficiency of the punishment of incest. Further, this study also analyse the effectiveness of the law of incest in Scotland as well as Ireland with regards to the ruling and procedure of the law in dealing with this offence. Based on the findings and the research conducted, this study suggest several recommendations that could aid in improving the current law of incest for a better enforcement of the law and act as an effective deterrence against the occurrence of incest cases. It is hoped that this research will create an awareness of incest as well as open up possibilities for a better regulation in dealing with incest.